Prognosis Mortalitas Pasien Tuberkulosis dengan Komorbid Diabetes Melitus Tipe 2: Analisis - Kemal Akbar Suryoadji; Ahmad Fauzi; Alifaturrasyid Syafaatullah Ridwan; Abdul Hafiidh Surya Putra; Wismandari Wisnu (Cermin Dunia Kedokteran, 2025)
Introduction: Indonesia ranks 3rd in tuberculosis (TB) cases in the world, and data from the Ministry of Health in 2020 showed that 10%-15% of TB sufferers had diabetes mellitus (DM). TB is one of the important causes of death, and DM affects the immune system which can increase the severity and mortality of the disease. This evidence-based case report was conducted to examine the mortality risk of tuberculosis patients with DM comorbidity. Methods: An article search was conducted to answer research questions based on 3 databases: PubMed, Cochrane, and ScienceDirect with the keywords “((Tuberculosis) AND (DM type 2) AND (Mortality))”. The search was based on inclusion and exclusion criteria and a critical review was conducted according to the guidelines for prognostic studies. Result: Tuberculosis patients with type 2 DM comorbidities have a 1.51 times higher risk of mortality compared to tuberculosis patients without type 2 DM comorbidities. Conclusion: Study by Huangfu, et al, (2019) can be the best choice to answer the clinical question that the risk of death of tuberculosis patients with comorbid DM increases by 1.51 times compared to patients without DM.